The influence of dietary protein and energy levels on the performance, meat bone ratio and meat chemical composition of SenSi-1 Agrinak chicken - Cecep Hidayat; Sofjan Iskandar (Jurnal Ilmu Ternak dan Veteriner, 2019)
Sensi-1 Agrinak is a strain of the improved native chickens for meat production in Indonesia. The objective of this study  was to investigate influence of different dietary energy and protein levels on performance, meat bone ratio, and meat chemical composition of Sensi-1 Agrinak chicken, reared until 10 weeks of age. Two hundred and sixteen of unsexed day old chickens (DOC) of  Sensi-1 Agrinak were subjected to six experimental rations differed in dietary crude protein (CP) content,. Namely: 21;19; and 17 % and dietary  metabolizable  energy (ME) (2800 and 3000 kcal/kg). Each treatment combination was replicated  four times and fed from day old to 10 weeks old. In each treatment combination there were nine unsexed-DOCs. The parameters observed were performance (i.e. live weight, feed intake, viability, FCR), economic index (European Production Efficiency Factor/EPEF), meat bone ratio, and meat chemical composition.  Result showed that  increased of dietary CP level increased live weight and EPEF (p<0.05). Sensi-1 Agrinak chicken had the best FCR (2.59), when fed  diet containing 21% CP and 3000 kcal/kg. Increased dietary CP level increased the  meat-bone ratio of breast, thighs, and drumsticks. Meanwhile, increased levels of dietary CP and ME did not affect (p>0.05) meat chemical composition. It is concluded that optimal dietary levels of crude protein and energy for unsexed Sensi-1 Agrinak chicken  up to 10 weeks of age were 21% CP and 3000 kcal/kg.